Designing Trustworthy Monitoring Systems: Forensic Readiness for Safety and Security - Watson, Venesa; Bajramovic, Edita; Bejiga, Mahlet; Waedt, Karl (Proceedings - 12th International Conference on Reliability, Maintainability, and Safety, ICRMS 2018, 2019)
A monitoring system is typically used to report on the resources and performance of a single system or a network of systems, and itself. Particularly in large, distributed networks, heavy reliance is placed upon monitoring systems to guide human behavior. For instance, the monitoring systems use special indicators to signal an impending or actual event. To address the growing instances of safety and security events in critical infrastructure, monitoring systems are increasingly being designed to target traditional attack vectors. However, consideration must be given to emerging events described as cyber-pranks, which are deliberate actions used to merely mimic an attack that could cause panic or even severe safety events accidentally triggered by the reactive actions of employees. For this paper, a cyber-prank is simulated on an I&C system, then the corrective actions based on the triggered event and the implications of these actions are examined. Modeling of all safety and security related artefacts is needed to assess and simulate the impact of security events on functional safety and nuclear safety. Discussions focus on measures to discern a cyber-prank from an actual attack, and how forensic-readiness can provide additional support in guiding incident response.
CRIS-Team Scopus Importer:2019-06-21
Keywords: cyber-pranks; human behavior; modeling; monitoring system; security events